POLITENESS IN THE LIMELIGHT: A CASE STUDY OF CHARLIE PUTH’S INTERVIEW ON “THE ELLEN SHOW” - Ilmi, Assayyidah Bil Ichromatil (Department of English Literature, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study aims to identify the politeness strategies present in the highly popular US show, The Ellen Show, where Charlie Puth appeared as a guest star. The research utilized qualitative methods, focusing on audio-visual data from The Ellen Show's YouTube channel. The analysis focused on two aspects: the politeness strategies used by the interviewer (Ellen) and those employed by the guest star (Charlie Puth). The findings of the study indicate a significant difference in the politeness strategies used by the host and the guest star. Ellen, as the presenter, predominantly utilized